热传导偏微分方程的求解

heat-flow problem solution ∂ T ‾ ∂ t ‾ = ∂ 2 T ‾ ∂ x ‾ 2 \frac{\partial \overline{T}}{\partial\overline{t}}=\frac{\partial^2 \overline{T}}{\partial\overline{x}^2}

By seperation law, assume
u ( x , t ) = X ( t ) T ( t ) u n ( x , t ) = X n ( t ) T n ( t ) u = ∑ n = 1 ∞ u i ( x , t ) = ∑ n = 1 ∞ a i X i ( t ) T i ( t ) ∂ u ∂ t = X d T d t , ∂ 2 u ∂ X 2 = T d 2 X d x , ∂ u ∂ t = ∂ 2 u ∂ x 2 X d T d t = T d 2 X d x u(x,t)=X(t)T(t) \\ u_n(x,t)=X_n(t)T_n(t)\\ u=\sum_{n=1}^{\infin}u_i(x,t)=\sum_{n=1}^{\infin}a_iX_i(t)T_i(t)\\ \frac{\partial u}{\partial t}=X\frac{dT}{dt}, \frac{\partial ^2u}{\partial X^2}=T\frac{d^2X}{dx}, \frac{\partial u}{\partial t}=\frac{\partial^2 u}{\partial x^2}\\ X\frac{dT}{dt}=T\frac{d^2X}{dx}
→ 1 T d T d t = 1 x d 2 X d x 2 = C ( w h e r e C i s a c o n s t a n t ) \rightarrow \frac{1}{T}\frac{dT}{dt}=\frac{1}{x}\frac{d^2X}{dx^2}=C (where C is a constant)
Case 1: positive constant \lambda^2 >0
1 T d T d t = 1 x d 2 X d x 2 = λ 2 d T d t = λ 2 T → T ( t ) = A e λ 2 t d 2 X d x 2 = λ 2 x → X ( x ) = B e λ x + C e − λ x ∴ u = A e λ 2 t ( B e λ x + C e − λ x ) u ( 0 , t ) = e λ 2 t ( B + C ) = 0 → B + C = 0 u ( 1 , t ) = e λ 2 t ( B e λ + C e − λ ) = 0 i f λ = 0 , i t i m p l i e s u i s i d e n t i c a l l y 0 i f λ ≠ 0 , ( B e λ + C e − λ ) = 0 w h i c h d o e s n ′ t e x i s t . \frac{1}{T}\frac{dT}{dt}=\frac{1}{x}\frac{d^2X}{dx^2}=\lambda^2\\ \frac{dT}{dt}=\lambda^2T \rightarrow T(t)=Ae^{\lambda^2t}\\ \frac{d^2X}{dx^2}=\lambda^2x \rightarrow X(x)=Be^{\lambda x}+Ce^{-\lambda x}\\ \therefore u = Ae^{\lambda^2t}(Be^{\lambda x}+Ce^{-\lambda x})\\ u(0,t)=e^{\lambda^2t}(B+C)=0 \rightarrow B+C=0\\ u(1,t)=e^{\lambda^2t}(Be^{\lambda}+Ce^{-\lambda})=0\\ if \lambda=0,it implies u is identically 0 \\ if \lambda \neq 0,(Be^{\lambda}+Ce^{-\lambda})=0which doesn't exist.

Case 2: constant=0
1 T d T d t = 0 → T = A 1 x d 2 X d x 2 = 0 → X = B x + C u ( 0 , t ) = A C = 0 u ( 1 , t ) = A B + A C = 0 → A B = 0 ∴ u ( x , t ) = 0 \frac{1}{T}\frac{dT}{dt}=0\rightarrow T=A\\ \frac{1}{x}\frac{d^2X}{dx^2}=0\rightarrow X=Bx+C\\ u(0,t)=AC=0\\ u(1,t)=AB+AC=0\rightarrow AB=0\\ \therefore u(x,t)=0\\
Case 3: constant is negative
1 T d T d t = − λ 2 → d T d t = − λ 2 T ∴ T ( t ) = e − λ 2 t 1 x d 2 X d x 2 = − λ 2 → d 2 X d x 2 = − λ 2 x ∴ X ( x ) = B c o s ( λ x ) + C s i n ( λ x ) ∴ u ( x , t ) = e − λ 2 t ( B c o s ( λ x ) + C s i n ( λ x ) ) \frac{1}{T}\frac{dT}{dt}=-\lambda^2\rightarrow \frac{dT}{dt}=-\lambda^2T\\ \therefore T(t)=e^{-\lambda^2t}\\ \frac{1}{x}\frac{d^2X}{dx^2}=-\lambda^2\rightarrow \frac{d^2X}{dx^2}=-\lambda^2x\\ \therefore X(x)=Bcos(\lambda x)+Csin(\lambda x)\\ \therefore u(x,t)=e^{-\lambda^2t}(Bcos(\lambda x)+Csin(\lambda x))\\

Acoording to the boundary condition
u ( 0 , t ) = e − λ 2 t B = 0 → B = 0 u ( 1 , t ) = e − λ 2 t C c o s ( λ x ) = 0 → C = 0 o r λ = n π , n = 0 , 1 , 2 , 3... u ( x , t ) = ∑ n = 1 ∞ a n s i n ( λ n x ) e − λ n 2 t u(0,t)=e^{-\lambda^2t}B=0 \rightarrow B=0\\ u(1,t)=e^{-\lambda^2t} Ccos(\lambda x)=0\rightarrow C=0 \\ or \lambda= n\pi, n=0,1,2,3...\\ u(x,t)=\sum_{n=1}^{\infin}a_nsin(\lambda_n x)e^{-\lambda _n^2t}\\
Acoording to the initial condition
u ( x , 0 ) = ∑ n = 1 ∞ a n s i n ( λ n x ) = ϕ ( x ) u(x,0)=\sum_{n=1}^{\infin}a_nsin(\lambda_n x)=\phi(x)\\
According to the theorem
ϕ ( x ) = ∑ n = 1 ∞ a n e 0 s i n ( λ n x ) = ∑ n = 1 ∞ a n s i n ( λ n x ) ∫ 0 ∞ ϕ ( x ) s i n ( λ n x ) d x = ∑ n = 1 ∞ ∫ 0 ∞ a n s i n ( λ n x ) s i n ( λ n x ) d x = ∑ n = 1 ∞ ∫ 0 ∞ a n ( s i n 2 λ n x ) d x = a n 2 ∴ a n = 2 ∫ 0 1 ϕ ( x ) s i n ( λ n x ) d x \phi(x)=\sum_{n=1}^{\infin}a_ne^0sin(\lambda_n x)=\sum_{n=1}^{\infin}a_nsin(\lambda_n x)\\ \int_{0}^{\infin}\phi (x)sin(\lambda_n x)dx\\ =\sum_{n=1}^{\infin}\int_{0}^{\infin}a_nsin(\lambda_n x)sin(\lambda_n x)dx\\ =\sum_{n=1}^{\infin}\int_{0}^{\infin}a_n (sin^2\lambda_nx)dx\\ =\frac{a_n }{2}\\ \therefore a_n=2\int_{0}^{1}\phi(x)sin(\lambda_nx)dx

04-01
03-12 671
03-18 135
12-07
03-25
01-18
07-19
07-15 1034
11-10